ALGORITMA POLINOMIAL MINIMUM UNTUK MEMBENTUK MATRIKS DIAGONAL DARI MATRIKS PERSEGI - Himmatul Mursyidah (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
In mathematics, matrices have many uses, they are finding solutions of a linear equation system, looking for specific solutions of differential equations, determining state classification on Markov chains, and so on. There is a special matrix in matrix theory, that is a diagonal matrix. The diagonal matrix is a matrix whose all non-diagonal entries are primarily zero so that the product of the diagonal matrix can be computed by considering only the components along the main diagonal. A square matrix can sometimes be formed into a diagonal matrix. If a non-diagonal square matrix A can be conjugated with a diagonal matrix, then there is an invertible matrix P so PAP-1=D, where D is a diagonal matrix and P is said to diagonalize A. To find a square matrix diagonalizable or not, many researchers usually use eigenvalues and eigenvectors evaluation. In this study, we discuss that the other way to form a diagonal matrix by using Minimum Polynomial Algorithm.